Pelatihan Manajemen Keuangan bagi Ibu Rumah Tangga di Desa Situ Gadung Kabupaten Tangerang - Ria Rosalia Simangunsong; Yeti Kusmawati; Ratih Andalusi (Jurnal PKM Manajemen Bisnis, 2026)
Financial management is a crucial skill for improving household welfare, yet many housewives face challenges in managing their income effectively. In Desa Situ Gadung, Tangerang Regency, housewives who run small businesses often lack formal knowledge of financial planning, budgeting, and saving strategies. This community service program aimed to enhance the financial management skills of housewives to support their economic empowerment and improve household financial stability. The program was conducted on August 19, 2025, at Desa Situ Gadung and involved nine lecturers from Universitas Pamulang as facilitators. The participants consisted of 30 local traders around the school area. The implementation of the program followed a structured approach, starting with preparation, followed by the main activities, and concluding with reporting. The core activities included interactive lectures, practical exercises, group discussions, and question-and-answer sessions, designed to provide participants with both theoretical understanding and hands-on experience in financial management. The results of the program indicated a significant improvement in participants’ knowledge and skills related to budgeting, expense tracking, and saving practices. Participants demonstrated increased confidence in managing their household finances and expressed motivation to apply the acquired skills in their daily business activities. This program highlights the importance of community-based financial education in empowering housewives and promoting sustainable local economic development.